Good English Pronunciation Users and Their Pronunciation Learning Strategies - Szyszka, Magdalena (Research in Language, 2015)
The study investigates pronunciation learning strategies (PLS) deployed by those with good English pronunciation, as well as their beliefs concerning the variables that affect pronunciation competence. In order to collect data for analysis this study surveyed 61 participants who had learned English as a foreign language. They comprised 28 higher education teachers and scholars specialising in English phonetics and phonology, who were defined as good pronunciation users (GPU), and 33 EFL teacher training students, viewed as average pronunciation learners (APL). This cohort responded to a survey on pronunciation learning strategies and expressed their views on several aspects affecting the L2 pronunciation learning process. These aspects were: age of the first contact with L2 (age of onset), motivation, exposure to the target language, the teacher’s pronunciation model, and learning strategies. The study used both open- and close-ended question formats to collect data from both GPU and APL. The analyses of the data helped to create a tentative profile of a successful L2 pronunciation learner.